2015
DOI: 10.3171/2014.9.jns141088
|View full text |Cite
|
Sign up to set email alerts
|

Sellar and parasellar tumor removal without discontinuing antithrombotic therapy

Abstract: results Gross-total removal of the tumor or total aspiration of the content of Rathke's cleft cyst was achieved in 13 patients, and subtotal removal was achieved in 1 patient with a small remnant in the cavernous sinus. No difference was found in intraoperative bleeding between the antithrombotic agent group and the control group (mean 255 ml vs 215 ml, Mann-Whitney U-test, p = 0.547), and no patient required transfusion. No difference was found in operation time between the antithrombotic agent group and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…In this study, the patients who continued ASA during the perioperative period demonstrated a trend for increased blood loss during the surgery 12). However, this did not result in increased risk of postoperative hemorrhage or the rate of reoperation 12). With regard to the effect of antiplatelet agents on postoperative hemorrhage after DC, Schuss et al17) reported that preoperative use of ASA was the only risk factor in patients with acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…In this study, the patients who continued ASA during the perioperative period demonstrated a trend for increased blood loss during the surgery 12). However, this did not result in increased risk of postoperative hemorrhage or the rate of reoperation 12). With regard to the effect of antiplatelet agents on postoperative hemorrhage after DC, Schuss et al17) reported that preoperative use of ASA was the only risk factor in patients with acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 64%
“…There were no statistical differences between the groups in outcomes, including bleeding complications, need for reoperation, or thrombotic complications in this retrospective cohort analysis 15). Ogawa and Tominaga12) reported 15 consecutive patients with sellar and parasellar tumors who had undergone transsphenoidal surgery without discontinuation of antiplatelet agent or anticoagulant therapy in 2015. In this study, the patients who continued ASA during the perioperative period demonstrated a trend for increased blood loss during the surgery 12).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…12 Two other studies confirmed these findings and consider brain tumor surgery safe with continuation of ASA treatment during the perioperative phase. 24,27 Early ASA resumption or even continued perioperative intake was shown to be safe for burr-hole drainage in chronic subdural hematoma (cSDH) as well as shunt placement. 9,10,14,15,17 To our knowledge, there are no randomized controlled trials (RCTs) analyzing bleeding risk with continued perioperative AP/AC treatment in neurosurgery.…”
Section: Management Of Ap/ac Treatment In Neurosurgical Patientsmentioning
confidence: 99%
“…Conversely, Ahmed et al found no signifi cant differences in hemorrhagic or thrombotic complications in craniotomy patients who either stopped aspirin perioperatively or continued to take it up to and through the operation [ 36 ]. Another study found no increase in the risk of hemorrhage in transsphenoidal operations for sellar and parasellar lesions [ 37 ]. Pending much more study, the only reasonable recommendation is to wait 5 days postoperatively, or until the individual physician feels the risk is acceptable.…”
Section: Postoperative Resumption Of Antiplatelet and Anticoagulant Amentioning
confidence: 98%